LANGUAGE USE BY STAFF AT KOMINFO IN PROVIDING INFORMATION VIA SOCIAL MEDIA PLATFORMS - C.N, Ana Astrini; Riny Jefri; Abdullah (International Journal of Business English and Communication, 2025)
This research aims to determine the language used by the Makassar City Communications and Information Service in conveying information via social media. Knowing the extent of the language understood by the public in conveying information. This study used descriptive qualitative method. Data collection techniques use observation and observation checklists. The results of this research show that the use of Communication and Information communication language really helps the public in increasing understanding. To develop and attract public interest and public awareness about government policies, programs and initiatives. They can use creative and relevant language to attract users' attention and convey important messages effectively. The way Kominfo staff use language on social media plays a very important role in the public's understanding of the information disseminated on social media, there are six functions of language, namely: regulatory function, intersectional function, instrumental function, personal function, heuristic function, which helps the use of language used by Kominfo on social media.